Honor Killing: Tackling an Abhorrent Crime Against Pakistani Women: Challenges, Hopes and Obstacles (Al-Qamar, 2021)
Customs and traditions are a reflection of a society's values. Culture, traditions and social ills are two different things; culture exists in a particular region and has existed for a long time and includes the values, food, pageantry, costumes as well as traditions, which are happy as well as sorrowful. However, with time, when a pure culture is intruded by social evils, ill traditions and harmful rituals, culture declines and degenerates. Several inhumane rituals such as Karo-Kari, Vani, Honor killings, and underage marriage shave, unfortunately, become deep rooted in Pakistani culture. Most of these atrocious and vicious practices especially “honor killing", are seemingly impossible to eradicate in the near future despite serious efforts being made by all organs of the society. Obviously, there is no religious or cultural sanction to this dreadful practice which, by all standards, is a heinous crime. It, however, has become a serious social concern. The western mind has always been fascinated by traditional dominant societies which perceives that such societies think and act within permanent cultural constraints. Even though the world is progressing, society is yet sticking to some of archaic customs and practices. It has stifled logical thoughts while encouraging aggressive behavior, all of which constitutes a violation of humanity. Women's rights, which are protected by laws, conventions, and treaties, have always been supported by the International for a and protected by Islamic rules; nonetheless, few societies still remain oblivious to women’s rights and dignity and keep on transgressing these, most of the time, with impunity. This paper discusses the crime of honor killing in Pakistan and analyzes the same through an Islamic lens as it is incorrectly presumed that honor killings are sanctioned by Islam. This research paper, it is hoped, will help in eradicating honor killings as well as adding to the current knowledge on the subject.
Keywords: Customs and traditions; Society; Honor killing; Pakistani culture; Women; Civilization; Islamic teachings